Liberalism in the Perspective of Hamid Fahmy Zarkasyi: A Descriptive Analytical Study - Amir Sahidin; Zahratur Rofiqah Binte Mochamad Sandisi (Journal of Islamic and Occidental Studies, 2025)
When the thought of religious liberalism entered Indonesia, some scholars regarded it as an idea for Islamic reform, resulting in confusion (shubhat) among the Muslim community. As the liberalization movement grew more widespread, Hamid Fahmy Zarkasyi emerged as one of the Muslim scholars at the forefront in rejecting the idea of liberalism through a rational and well-argued approach. Therefore, this article discusses liberalism from the perspective of Hamid Fahmy Zarkasyi. Through library research and descriptive analysis, it can be concluded that: first, liberalism is a Western worldview that presupposes absolute freedom whether in politics, society, economy, thought, or religion. Second, the liberalization of Islamic thought is a joint movement between missionaries, orientalists, and colonialists, which was later adopted by liberal scholars. Third, the challenges of liberalism encompass five aspects, namely: the doctrines of relativism, pluralism, feminism and gender, criticism of the Qur'an, and the deconstruction of Islamic law (sharia).